2022
DOI: 10.3390/math10020195
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Spread Forecasting, Mathematical Methods vs. Machine Learning, Moscow Case

Abstract: To predict the spread of the new coronavirus infection COVID-19, the critical values of spread indicators have been determined for deciding on the introduction of restrictive measures using the city of Moscow as an example. A model was developed using classical methods of mathematical modeling based on exponential regression, the accuracy of the forecast was estimated, and the shortcomings of mathematical methods for predicting the spread of infection for more than two weeks. As a solution to the problem of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The findings imply that the logistic growth model best describes the pandemic's behavior, that there is sufficient correlation between climatic and movement factors and illness numbers, and that the Long Short-Term Memory (LSTM) network may be successfully used to forecast daily cases. A similar comparison of forecasting methodologies for the same task was performed in [9]. The classical methods of mathematical modeling in this case showed some weaknesses.…”
Section: Introductionmentioning
confidence: 77%
“…The findings imply that the logistic growth model best describes the pandemic's behavior, that there is sufficient correlation between climatic and movement factors and illness numbers, and that the Long Short-Term Memory (LSTM) network may be successfully used to forecast daily cases. A similar comparison of forecasting methodologies for the same task was performed in [9]. The classical methods of mathematical modeling in this case showed some weaknesses.…”
Section: Introductionmentioning
confidence: 77%
“…The results show that in majority cases LSTM outperforms other models. In another recent comparative study LSTM-based forecasting model outperformed CNN and exponential regression models [67] .…”
Section: Deep Learning Models For Covid-19 Forecastingmentioning
confidence: 99%
“…LSTM was shown to outperform other models. Egypt; Feb - Aug, 2020 0.9998 Pavlyutin et al, 2022 [67] Compared long-term (48 days) forecasting accuracy of LSTM, CNN, and exponential regression models and found the LSTM to be the best. Moscow city; Oct - Dec, 2021 5.4 Rguibi et al, 2022 [73] Compared LSTM and ARIMA models and found similar performance.…”
Section: Deep Learning Models For Covid-19 Forecastingmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the mechanism of the pandemic's spread, several models have been used, including statistical [ 9 ], mathematical [ 10 – 15 ], computational simulation [ 16 – 18 ], and numerical simulation [ 19 21 ]. The techniques of machine learning [ 22 25 ] and Big Data are also used [ 26 – 28 ]. The first and the most popular model is called the suspected, infected and recovered individuals model (SIR model) [ 29 32 ].…”
Section: Introductionmentioning
confidence: 99%